Association of nonalcoholic fatty liver disease and liver fibrosis detected by transient elastography with serum retinol in American adults - Niu, Xiaoxian; Liu, Jian; Liu, Kai (Frontiers in Nutrition, 2023)
Background & Objective: Retinol is a precursor of vitamin A, which is metabolised and maintained in the liver and is involved in the pathogenesis of nonalcoholic fatty liver disease (NAFLD) and liver fibrosis. The relationship between NAFLD and liver fibrosis with serum retinol levels remains insufficient and inconclusive. Our study aimed to investigate the correlation between NAFLD, fibrosis, and serum retinol levels in American adults. Methods: A cross-sectional analysis was conducted using information from the 2017–18 cycle of the National Health and Nutrition Examination Survey (NHANES). The exposure factors were NAFLD and liver fibrosis status detected using transient elastography (TE), and the outcome was serum retinol levels. Weighted multivariate regressions were established to assess the correlation between NAFLD and liver fibrosis and serum retinol levels. Subgroup analyses were also performed. Results: This study included 3537 participants. Compared to the group without NAFLD, NAFLD was positively correlated with serum retinol levels (β = 1.28, 95% CI: 0.19, 2.37). In the subgroup analysis, a positive correlation between NAFLD and serum retinol levels was found in people aged < 60 years, Mexican Americans, and those with a body mass index (BMI) < 25. Contrarily, compared to the group without liver fibrosis, there was a significant negative association between liver fibrosis and serum retinol (β = -3.46, 95% CI: -5.16, -1.75), especially in people aged < 60 years, non-Hispanic White/Black individuals, and people with a BMI ≥ 25. Conclusion: Our study suggests that NAFLD status may be positively associated with serum retinol levels in adult patients, and liver fibrosis may be negatively associated with serum retinol levels. Further studies are required to examine the associations found in our study.